Agronomic Characters Plant and Potential of Strain Rice (Oryza Sativa L.) Which Formed in The Three Generations (F3) - Jamaludin Adimiharja; Jaenudin Kartahadimaja; Eka Erlinda Syuriani (Politeknik Negeri Lampung., 2017)
The formation of high-yielding varieties are required to have the advantage of being more diverse and more specific, according to the agro-ecosystem. Assembling new rice strains that have high yield and adaptive in different agro-ecosystem is a solution that should be done. The research objective was to determine the appearance of agronomic characters and yield potential of 11 new rice lines in the 3rd generation (F3). The study was conducted in paddy fields belonging Polinela, in January to May 2015. The study using randomized block design (RBD), as the treatment is 11 new rice lines repeated three times. The variables measured were the growth parameters and yield components. Data were analyzed by analysis of variance, if there is a difference between the treatment, the test is done with the Advanced Test Honestly Different (HSD) 5%. Based on the research that has been done toeleven new rice lines have different agronomic characters and has the lowest yield potential ton.ha 6.7-1, and the highest 10.4 ton.ha-1.Keywords: agronomic character, yield potential, new rice lines